Signatures of Mass Segregation from Competitive Accretion and Monolithic Collapse - Richard J. Parker; Emily J. Pinson; Hayley L. Alcock; James E. Dale (The Astrophysical Journal, 2024)
The two main competing theories proposed to explain the formation of massive (>10 M _⊙ ) stars—competitive accretion and monolithic core collapse—make different observable predictions for the environment of the massive stars during, and immediately after, their formation. Proponents of competitive accretion have long predicted that the most massive stars should have a different spatial distribution to lower-mass stars, through the stars being either mass segregated or being in areas of higher relative densities or sitting deeper in gravitational potential wells. We test these predictions by analyzing a suite of smoothed-particle hydrodynamics simulations where star clusters form massive stars via competitive accretion with and without feedback. We find that the most massive stars have higher relative densities, and sit in deeper potential wells, only in simulations in which feedback is not present. When feedback is included, only half of the simulations have the massive stars residing in deeper potential wells, and there are no other distinguishing signals in their spatial distributions. Intriguingly, in our simple models for monolithic core collapse, the massive stars may also end up in deeper potential wells because if massive cores fragment then the stars that form are also massive, and dominate their local environs. We find no robust diagnostic test in the spatial distributions of massive stars that can distinguish their formation mechanisms, and so other predictions for distinguishing between competitive accretion and monolithic collapse are required.